Congenital long QT syndrome - Melgar Quicaño, Luis (2021)
Congenital long QT syndrome (LQTS) represents a group of heart diseases of genetic origin characterized by prolongation of the QT interval and an abnormal T wave on the electrocardiogram (ECG). They can have a dominant or recessive expression, the latter associated with sensorineural deafness. In both cases, its clinical presentation is associated with recurrent syncope and sudden death as a consequence of ventricular tachycardia, specifically Torsades de Pointes. Currently they are classified according to the specific genetic defect, being able to compromise around 16 genes and almost 2000 mutations. It should be suspected in individuals with related symptoms, electrocardiographic findings, and family history. Management is based on the reduction or elimination of symptoms, and concomitantly the prevention of sudden death (SD), in those children with congenital deafness, the management requires the application of the otolaryngologist specialist's own measures. The cardiovascular management implies the modification of lifestyles, mainly the prohibition of competitive sports, including swimming, avoiding exposure to loud sounds or triggers. The medications used include beta-blockers, and more rarely flecainide, ranozaline, and verapamil; invasive management consists of the implantation of a cardioverter defibrillator or even left sympathetic denervation, each with its own risks and benefits. In any of the cases, we must avoid the circumstances that increase the QT interval, as well as carry out the appropriate analysis of the benefits and risks of each possible invasive measure.